RAVE stars in K2: I. Improving RAVE red giants spectroscopy using asteroseismology from K2 Campaign 1 - Valentini, Marica; Boeche, Corrado; Grebel, Eva K. (Astronomy and astrophysics, 2017)
Astronomy & Astrophysics (A&A) is an international journal which publishes papers on all aspects of astronomy and astrophysics
Gesehen am 04.09.2017